Changing Imperatives in Workforce Planning: Implications for Health and Social Care Education - Gosling, Sally (International Journal of Practice-based Learning in Health and Social Care, 2016)
Workforce planning forms an increasing focus within health and social care policy and structural development, with concern to ensure that workforce supply demonstrably meets demand (in terms of population, patient, service and practice needs). While particularly apparent in England, this trend can be seen elsewhere in the United Kingdom. This article considers the implications of this trend for health and social care education, including practice education. Although having a particular emphasis on challenges and opportunities for the allied health professions, the article considers the issues more generically. Workforce planning is now seen within policy as key to addressing priority population and patient care needs; achieving service improvements while containing expenditure; and ensuring that patient needs are put first. The size, profile and skills development of the workforce is therefore being placed centre-stage in order to enhance service design and delivery, assure clinical and cost-effectiveness, and deliver compassionate care. These developments raise both challenges and opportunities for education providers. Within curriculum design and delivery, an increasing focus is needed on developing the knowledge, skills and aptitude required for clinical leadership and inter-professional collaboration, and on evidencing the value, impact and professionalism of individual practitioners, services and professions. This is producing a related, stronger focus on how practice education prepares future members of the workforce for more flexible, diverse roles in safe, patient-centred ways. New approaches to workforce planning are creating increased opportunity for education to demonstrate how it both responds to and leads change, while affirming quality assurance imperatives.